Enhancing the quality and technological properties of goose meat during low-temperature storage through the action of biologically active substances from oats and alfalfa - Maiboroda, Daniil; Danchenko, Olena; Gryshchenko, Viktoriya; Danchenko, Mykola (Eastern-European Journal of Enterprise Technologies, 2024)
Poultry meat plays a key role as a source of high-quality protein, vitamins, minerals, and unsaturated fatty acids. However, unsaturated fatty acids, especially essential ones, are prone to oxidative reactions during meat storage, which can negatively affect its quality. The object of the study is the technology of obtaining and storing poultry meat. Legart Danish geese were used as the experimental material. Oats (Avena Sativa) and alfalfa (Medicago sativa) contain a large number of biologically active substances (minerals, unsaturated fatty acids, amino acids, antioxidants). Adding vegetative parts of oats and alfalfa to the diet of geese contributes to improving the quality of the obtained meat, especially after prolonged low-temperature storage. The geese were slaughtered on the 63rd day. The meat was stored at a temperature of –18 °C for 90 days. It was found that there was an 11.5 % increase in the live weight of the geese at an early slaughter age, an increase in protein content (by 5 %), better moisture-binding capacity (by 6–7.3 %), and a decrease in the content of lipid peroxidation products, especially on the 67th day of storage (28.3 %). There was a significant increase in the content of ω3 and ω6 polyunsaturated fatty acids (by 24.2 % and 10.8 %, respectively). There was an increase in the content of vitamin E and β-carotene, both before freezing (38.5 % and 19.6 %) and at the end of the storage period (50.9 % and 20 %). A tendency to increase the content of essential amino acids (threonine and methionine) was found. The results can be used in the production of goose meat to improve its nutritional characteristics, which is important for the health of consumers, meat producers, and also in scientific research on the development of technologies in the field of meat production and storage